PENGARUH DEBT TO ASSET RATIO DAN DEBT TO EQUITY RATIO TERHADAP KINERJA - Lisa Amelia; Henryanto Wijaya (Jurnal Paradigma Akuntansi, 2023)
This study has one goal, to see whether there is a relationship between DebtttooAssett Ratiooand Debtt tooEquityyRatiooto ReturnnonnAssets, ReturnnonnEquity, Earning per Sharing and Tobins'q with companies engaged in manufacturing that are listed on the IDX in year 2018-2020. With 57 companies sampled in the purposive sampling method with panel data regression analysis using the EVIEWS version 10 program and Microsoft excel 2019. Which shows that the Debt to Asset Ratio (DAR) does not have a significant negative effect on Return on Assets (ROA), (EPS) and Tobin's Q. Debt to Equity Ratio (DER) does not have a significant negative effect on Return on Assets (ROA) and Return on Equity (ROE). Debt to Asset Ratio (DAR) has no negative and insignificant effect on Return on Equity (ROE). Debt to Equity Ratio (DER) has a significant negative effect on EarninggPerrSharing (EPS). DebtttooEquityyRatio (DER) has an insignificant negative effecttonnTobin's Q. Theeimplicationnoffthissresearch is the company's financial performance that can influence investors in determining investment.